2000
DOI: 10.2307/1593055
|View full text |Cite
|
Sign up to set email alerts
|

Reticuloendotheliosis Virus (REV) Long Terminal Repeats Incorporated in the Genomes of Commercial Fowl Poxvirus Vaccines and Pigeon Poxviruses without Indication of the Presence of Infectious REV

Abstract: Because of reticuloendotheliosis virus (REV) contamination in commercial poultry vaccines, polymerase chain reaction (PCR) assays have been described to increase the sensitivity of biological assays used to detect REV in vaccines. The PCR assay designed to amplify the long terminal repeat (LTR) region of REV identified REV LTRs in many of the commercial fowl poxvirus (FPV) vaccines evaluated. These commercial vaccines were not thought to be contaminated with replicating REV because of the lack of REV outbreaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 26 publications
2
35
2
Order By: Relevance
“…Moreover, short nucleotide stretches exhibiting Ͼ70% homology with the R and U3 regions of the long terminal repeat (LTR) of the avian retrovirus reticuloendotheliosis virus (REV) have been found in the DNA of two serotype I oncogenic strains of Marek's disease virus (10). Likewise, remnants of the REV LTR have been retained in the genomes of all FPV vaccine strains so far examined (9,15,22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, short nucleotide stretches exhibiting Ͼ70% homology with the R and U3 regions of the long terminal repeat (LTR) of the avian retrovirus reticuloendotheliosis virus (REV) have been found in the DNA of two serotype I oncogenic strains of Marek's disease virus (10). Likewise, remnants of the REV LTR have been retained in the genomes of all FPV vaccine strains so far examined (9,15,22).…”
mentioning
confidence: 99%
“…Whether there was only one progenitor or others resulting from independent insertions is also a point of conjecture. However, it should be noted that this association with a retrovirus may be novel in avipoxviruses, since no REV sequences have been found in the DNAs of either canarypox virus, quailpox virus, or a field isolate of pigeonpox virus (13,15). Of equal interest is the origin of the attenuated strains currently used as vaccines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[62][63][64][65] These studies demonstrated that REV-inserted fragments into wild type field FPV isolates were variable in content, although they included the REV long terminal repeats (LTR) of various lengths, and also additional sections of the proviral genome. Although the REV genomic integrations into the FPV genome has been demonstrated only in the last 10 years, the analysis of previous field isolates indicated that such events occurred even 50 years ago.…”
Section: Pox and Retrovirusesmentioning
confidence: 99%
“…63,65 The inserted REV fragment into the FPV differed in composition between wild type FWPV and FWPV vaccine strains. While all the field isolates contained complete REV provirus or various fragments of the 3' and 5' REV-LTRs, in addition to other REV fragments, including the REV env gene, recent FPV vaccine strains included only the REV LTR.…”
mentioning
confidence: 99%